Disease mechanisms of X-linked retinitis pigmentosa due to RP2 and RPGR mutations. (19th October 2016) - Lyraki, Rodanthi; Megaw, Roly; Hurd, Toby
Abstract : Photoreceptor degeneration is the prominent characteristic of retinitis pigmentosa (RP), a heterogeneous group of inherited retinal dystrophies resulting in blindness. Although abnormalities in many pathways can cause photoreceptor degeneration, one of the most important causes is defective protein transport through the connecting cilium, the structure that connects the biosynthetic inner segment with the photosensitive outer segment of the photoreceptors. The majority of patients with X-linked RP have mutations in the retinitis pigmentosa GTPase regulator ( RPGR ) or RP2 genes, the protein products of which are both components of the connecting cilium and associated with distinct mechanisms of protein delivery to the outer segment. RP2 and RPGR proteins are associated with severe diseases ranging from classic RP to atypical forms. In this short review, we will summarise current knowledge generated by experimental studies and knockout animal models, compare and discuss the prominent hypotheses about the two proteins' functions in retinal cell biology.